Application of optically active chiral bis(imidazolium) salts as potential receptors of chiral dicarboxylate salts of biological relevance1. Issue 19 (21st May 2015) - González-Mendoza, Laura; Escorihuela, Jorge; Altava, Belén; Burguete, M. Isabel; Luis, Santiago V.
<x xml:space="preserve">Abstract</x> New chiral ionic liquids as receptors for dicarboxylic acid derivatives.